The complete mitochondrial genome of Tituria pyramidata (Hemiptera: Cicadellidae: Ledrinae) from China - De-Fang Li; Ren-Huai Dai (Mitochondrial DNA. Part B. Resources, 2020)
In this article, the complete mitogenome of Tituria pyramidata Cai, was sequenced and annotated, which contained 37 typical genes. The length of the mitochondrial genome is 15,331 bp with A + T% for the whole sequence = 75.6% (A = 29%, T = 46.6%, G = 13.7%, and C = 10.6%). Protein-coding genes (PCGs) started with standard start codon ATN (ATA, ATT, ATG, and ATC) and ended with TAR (TAA and TAG), except nad5 started with TTG, cox3 ended with single T. The phylogenetic tree confirms that T. pyramidata was clustered with Ledra auditura with strong branch support.